ANALISIS PENGARUH DISIPLIN KERJA, MOTIVASI KERJA, DAN LINGKUNGAN KERJA, TERHADAP KINERJA PEGAWAI, PADA KANTOR DISTRIK KUALA KENCANA KABUPATEN MIMIKA PROVINSI PAPUA TENGAH - Yohanis Iraratu; Yermin Gombo; Antje Tuasela (Jurnal Ekonomi dan Bisnis, 2025)
This study aims to determine: the eflect of work discipline, work motivation and work environment on employee performance at the Kuala Kencana District Office. The research method used in this study is the associative research method, which is a method to determine the relationship or influence between two or more variables. In this study, the data collection methods used are the observation method, questionnaire method and documentation method. To determine the positive influence between these variables, the analysis instrument used in this study is multiple linear analysis. The results of this study indicate that partially the variables of work discipline and work environment have a positive and significant eflect on employee performance, but work motivation does not have a significant eflect. The results of simultaneous testing show that work discipline, work motivation, and work environment have a significant eflect on employee performance.